1988
DOI: 10.1128/jcm.26.8.1524-1534.1988
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, genetic, and epidemiologic characterization of Haemophilus influenzae biogroup aegyptius (Haemophilus aegyptius) strains associated with Brazilian purpuric fever

Abstract: Brazilian purpuric fever (BPF) is a recently recognized fulminant pediatric disease characterized by fever, with rapid progression to purpura, hypotensive shock, and death. BPF is usually preceded by purulent conjunctivitis that has resolved before the onset of fever. Both the conjunctivitis and RPF are caused by Haemophilus influenzae biogroup aegyptius (formerly called H. aegyptius). Isolates from 15 BPF cases, mainly from blood or hemorrhagic cerebrospinal fluid, case-associated isolates from 42 persons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 30 publications
1
61
0
Order By: Relevance
“…The BPF clone was susceptible to many commonly used antibiotics, including ampicillin, cefuroxime, cefotaxime, rifampin, and chloramphenicol (11). In the Serrana outbreak, the initiation of parenteral antibiotics before the development of hemorrhagic skins lesions was associated with better survival (10).…”
Section: Clinical Features Of Bpfmentioning
confidence: 99%
See 4 more Smart Citations
“…The BPF clone was susceptible to many commonly used antibiotics, including ampicillin, cefuroxime, cefotaxime, rifampin, and chloramphenicol (11). In the Serrana outbreak, the initiation of parenteral antibiotics before the development of hemorrhagic skins lesions was associated with better survival (10).…”
Section: Clinical Features Of Bpfmentioning
confidence: 99%
“…In addition, DNA hybridization studies indicated that the two organisms are phylogenetically a single species (2). To account for both the clinical and phenotypic differences, as well as the phylogenetic similarities, the name H. influenzae biogroup aegyptius has been assigned to what was previously known as H. aegyptius (11). For both simplicity and historical reasons, however, we refer to the organism as H. aegyptius throughout this review.…”
Section: Nomenclature and Taxonomymentioning
confidence: 99%
See 3 more Smart Citations